Front Cover: How 5 f Electron Polarisability Drives Covalency and Selectivity in Actinide N‐Donor Complexes (Chem. Eur. J. 72/2021). Issue 72 (15th December 2021) - Köhler, Luisa; Patzschke, Michael; Schmidt, Moritz; Stumpf, Thorsten; März, Juliane
Abstract : N versus O donor : Isostructural complexes [An(pyren)2 ] (An=Th, U–Pu) with a pyrrole‐based ligand (pyren) were synthesised and compared to the structural relative salen. Solid‐state analysis and quantum chemical calculations reveal an increased bond strength to the imine nitrogen when changing the second donor from the dominant O to the softer N . In the complexes, the overall bond strength of salen exceeds pyren, except for the Pa case. This can be explained by a greater degree of polarizability for the Pa 5  f 1 state. More information can be found in the Full Paper by J. März et al. (DOI: 10.1002/chem.202102849 ).